Antiproliferative activity of standardized herbal phytopreparation from Asclepias subulata - González Gutiérrez, Francisco Humberto; Rascón Valenzuela, Luisa Alondra; Meneses Sagrero, Salvador Enrique; Dias-Silva, Marcelo J. [UNESP]; Valenzuela Antelo, Olivia; Velazquez, Carlos; Vilegas, Wagner [UNESP]; Robles Zepeda, Ramón Enrique (F1000Research, 2022)
Background: Several studies have shown that active compounds of Asclepias subulata (cardenolides) have antiproliferative effect on human cancer cells. Cardenolides isolated from A. subulata can be used as active chemical markers to elaborate phytopharmaceutical preparations. The aim of this work was to evaluate the antiproliferative effect of a standardized extract of the aerial parts, based on Asclepias subulata cardenolides. Methods: Four standardized extracts were prepared by HPLC-DAD depending on the concentration of calotropin and the antiproliferative activity was measured for the MTT assay, on the A549, MCF-7, HeLa, PC3 and ARPE cell lines. The concentrations of calotropin used for the standardization of the extracts were 10, 7.6, 5 and 1 mg/dL. Results: Standardization of the A. subulata extract based on calotropin at 7.6 mg/g dry weight was achieved and the antiproliferative activity was evaluated over A549, HeLa and MCF-7 cell lines, obtaining proliferation percentages of 3.8 to 13.4%. Conclusions: The standardized extracts of A. subulata at different concentrations of calotropin showed antiproliferative activity against all the cell lines evaluated. The greatest effect was observed against the HeLa cell line.
Keywords: Antiproliferative activity; Asclepias subulate; Calotropin; Cardenolides; Standardized extract